Nutritional Efficiency of Coffea canephora: The Role of Genetic Variability and Nutrient Accumulation - Cleidson Alves da Silva; Jéssica Rodrigues Dalazen; Weverton Pereira Rodrigues; Rodrigo Barros Rocha; Fábio Luiz Partelli (Plants)
The genetic variability of Coffea canephora is essential for the identification of genotypes with enhanced nutritional traits. This study aimed to characterize C. canephora genotypes based on nutrient accumulation in fruits, evaluated over two consecutive harvests. The experiment followed a randomized block design with four replications, comprising 42 genotypes. To assess nutrient accumulation, fruit samples were collected from each genotype and oven-dried. In a plant tissue analysis laboratory, the concentrations of N, P, K, Ca, Mg, S, Fe, Mn, Cu, Zn, and B were determined. Nutrient accumulation in the fruits was calculated as dry mass × nutrient concentration, and the data were converted to kg or g of nutrients accumulated per ton of coffee beans at 12% moisture content. The results revealed significant variability among genotypes in nutrient accumulation, with the general accumulation order being N > K > Ca > Mg > S > P > Mn > Fe > B > Cu > Zn. Multivariate analysis identified seven groups, with Verdim R, Clementino, and Pirata forming distinct clusters due to their unique characteristics. Clementino exhibited the highest nutrient accumulation, while LB1 had the lowest. The study demonstrated high heritability for all traits, indicating strong genetic control, along with significant positive correlations among nutrients. These findings highlight the potential of selecting nutrient-efficient genotypes to enhance the sustainability of coffee cultivation. The nutritional data obtained can support the development of more nutritionally efficient cultivars, ensuring long-term sustainability in coffee production.